Self–sealing hot isostatic pressing–diffusion bonding of titanium for near net shape manufacture - Garcia Hernandez, Alfonso C. (2019)
Diffusion bonding is a manufacturing process that has been largely used in industry in a variety of sectors and applications (casting, fan blades manufacturing, nuclear reactors components fabrication, etc.). The process is performed in a hot isostatic press (HIP) and requires encapsulation of the components to generate vacuum and stability in the assemblies. Encapsulation is typically accomplished by a canister, which needs the same shape, geometry and complexity of the final component. In this work, a novel manufacturing process was developed to eliminate the canister and replace its performance by a “Self-Sealing” HIP-Diffusion Bonding method, which is based in a series of welding steps with laser and electron beams that create an intermediate vacuum cavity for diffusion bonding. The concept of this novel process was developed and patented at the University of Nottingham with Rolls Royce sponsorship. The research project for this MPhil study aimed to validate this technology, taking into account that joining of massive titanium sections cut from plate is an attractive alternative to manufacturing of large components by forging, as it offers a simple route to near net shaping, reducing the overall cost of assemblies and parts. A collection of different geometries was tested and all results were set as the process standard. The tensile and fatigue properties of Ti-6-4-to-Ti-6-4, Ti-624-to-Ti-6246 and Ti-6-4-to-Ti-6246 bonded parts are presented and compared with HIPed bulk Ti. The effect of surface preparation on the bond strength is also presented. Overall, little to no decrement in the strength, and only a small decrease in fatigue life is observed as a result of the bonding process. In all cases, failure was observed away from the bond line and showed high levels of plastic deformation. The novel process has been shown to provide a robust, reliable and repeatable method for bonding similar and dissimilar Ti plates.